Emotion Regulation and Dating Violence On Students That Go Through Toxic Relationship - Christine Marcellin Young; Arthur Huwae (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Students who study in tertiary institutions are individuals who are starting to enter early adulthood. Dating is one of the important roles performed by individuals who are in the category of early adulthood. However, in a dating relationship, it is undeniable that various problems can arise. One of the problems that may arise is dating violence. It is common for dating violence in dating relationships to get individuals trapped in a toxic relationship. Various factors are considered the triggers of dating violence, one of which is low emotion regulation ability. This study aims to determine the relationship between emotion regulation and dating violence on students in Salatiga. This study uses a quantitative method with a correlational design involving 40 participants. The researcher obtained participants in this study through a simple random sampling technique. Data was collected using the emotion regulation scale and dating violence scale. The data analysis results showed a significant negative relationship between emotion regulation and dating violence with sig value. = 0.010 (p <0.05) and an r-value of -0.364.